Beyond the thermal model in relativistic heavy-ion collisions - Wolschin, Georg (Physical review, 2016)
Deviations from thermal distribution functions of produced particles in relativistic heavy-ion collisions are discussed as indicators for nonequilibrium processes. The focus is on rapidity distributions of produced charged hadrons as functions of collision energy and centrality, which are used to infer the fraction of particles produced from a central fireball as compared with that from the fragmentation sources that are out of equilibrium with the rest of the system. Overall thermal equilibrium would only be reached for large times t→∞.